2019
DOI: 10.1007/s10973-019-08844-y
|View full text |Cite
|
Sign up to set email alerts
|

Thermography assessment of spastic lower limb in patients after cerebral stroke undergoing rehabilitation

Abstract: Stroke contributes to disability in adulthood. The assessment of the degree of spasticity is one of the basic methods of patient examination after stroke and is used for monitoring rehabilitative outcomes; however, no optimal scale for the unambiguous assessment of spasticity exists. Our study aimed to assess the usefulness of thermography in measuring the effects of rehabilitation in stroke patients' spastic hemiparesis. In this prospective, single-center study, 40 stroke patients with a mean age of 60.6 ± 5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 30 publications
2
5
1
2
Order By: Relevance
“…However, other authors have proposed reference values lower than 32 °C in the same ROI [ 29 , 38 , 39 ]; however, the thermal values provided by these authors, i.e., 30.7 °C [ 38 ], 30.2 °C [ 29 ], and 30.7 °C [ 39 ], are still higher than the mean values obtained in this work. Thus, even using lower reference values, the thermographic results obtained in the affected patients would show non-conventional temperatures given that, in our study, the patients presented a mean temperature lower than 29.5 °C in both legs at both times, like the results of similar works by other authors [ 37 ].…”
Section: Discussionsupporting
confidence: 82%
“…However, other authors have proposed reference values lower than 32 °C in the same ROI [ 29 , 38 , 39 ]; however, the thermal values provided by these authors, i.e., 30.7 °C [ 38 ], 30.2 °C [ 29 ], and 30.7 °C [ 39 ], are still higher than the mean values obtained in this work. Thus, even using lower reference values, the thermographic results obtained in the affected patients would show non-conventional temperatures given that, in our study, the patients presented a mean temperature lower than 29.5 °C in both legs at both times, like the results of similar works by other authors [ 37 ].…”
Section: Discussionsupporting
confidence: 82%
“…Although no association between the studied variables of tactile sensibility and temperature differences was found, our results suggest that mechanoreceptors response may not be correlated with temperature control, which in turn may be correlated with the hypothalamus, which balances heat generation with heat loss, being connected to the pituitary gland at the base of the brain near to the termination of the brain stem 6 , 40 or even with the degree of spasticity and strength of the patient 41 .…”
Section: Discussioncontrasting
confidence: 66%
“…Once temperature is an indicator for many health conditions, it can be used to assess the vascular status in different body segments. Recent studies have used thermography as an assessment tool for individuals in rehabilitation treatment, such as for patients with stroke sequelae [8,9]. A recent study carried out by our group found that there is a significant association between sensorimotor recovery and differences in cutaneous temperature and differences in tactile sensibility between both sides of the body in people with stroke sequelae [10].…”
Section: Introductionmentioning
confidence: 99%